Algorithmic music for therapy - Raglio, Alfredo (2021)
Raglio, A., Baiardi, P., Vizzari, G., Imbriani, M., Castelli, M., Manzoni, S., Vico, F., & Manzoni, L. (2021). Algorithmic music for therapy: Effectiveness and perspectives. Applied Sciences (Switzerland), 11(19), 1-13. [8833]. https://doi.org/10.3390/app11198833 --------------------------------------------------------------Funding Information: Acknowledgments: This work was partially supported by FCT, Portugal, through funding of the project GADgET (DSAIPA/DS/0022/2018), and the financial support from the Slovenian Research Agency (research core funding no. P5-0410). Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.